Metabolic engineering of Klebsiella pneumoniae J2B for co-production of 3-hydroxypropionic acid and 1, 3-propanediol from glycerol: Reduction of acetate and other by-products. (November 2017) - Ko, Yeounjoo; Seol, Eunhee; Sundara Sekar, Balaji; Kwon, Seongjin; Lee, Jaehyeon; Park, Sunghoon
Highlights: K. pneumoniae was engineered for co-production of 3-HP and 1, 3-PDO from glycerol. Co-production improved upon by-products reduction. The maximum 21 g/L 1, 3-PDO and 43 g/L 3-HP were obtained in fed-batch bioreactor cultivation. Acetate accumulation was serious and limited further improvement of co-production. Activation of TCA cycle and ETC is suggested to reduce acetate and improve ATP supply. Abstract: Production of 3-hydroxypropionic acid (3-HP) or 1, 3-propanediol (1, 3-PDO) production from glycerol is challenging due to the problems associated with cofactor regeneration, coenzyme B12 synthesis, and the instability of pathway enzymes. To address these complications, simultaneous production of 3-HP and 1, 3-PDO, instead of individual production of each compound, was attempted. With over-expression of an aldehyde dehydrogenase, recombinant Klebsiella pneumoniae could co-produce 3-HP and 1, 3-PDO successfully. However, the production level was unsatisfactory due to excessive accumulation of many by-products, especially acetate. To reduce acetate production, we attempted; (i) reduction of glycerol assimilation through the glycolytic pathway, (ii) increase of glycerol flow towards co-production, and (iii) variation of aeration rate. These efforts were partially beneficial in reducing acetate and improving co-production: 21 g/L of 1, 3-PDO and 43 g/L of 3-HP were obtained. Excessive acetate (>150 mM) was still produced at the end of bioreactor runs, and limited co-production efficiency.